Contribution to the Promotion of Innovative and Climate-Smart Agroecology: Application to Agriculture and Livestock in the Haute Matsiatra Region, Madagascar - Rakotonirina M.D.L.; Razafindrazanakolona A.D.; Ramanampisoa V.E.; Rabesiaka R; Damy T.S.; Koto-te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina B.; Muhammad Ridwan (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2023)
Climate change (CC) is having negative impacts on agricultural production at global, national, and local scales. Climate risks to agriculture, livestock, and fisheries are expected to increase in the coming decades, particularly in low-income countries with low adaptive capacity such as those in Africa and Madagascar. In most African countries, agriculture must undergo a profound transformation to address the many challenges of CC, food insecurity, malnutrition, poverty, and environmental degradation. This "Climate Smart Agriculture (CSA)" or e-agriculture is an integrated approach to address the interrelated challenges of food security and climate change in order to achieve the objectives of adaptation or mitigation of climate change risks. Support for building resilience, support for community-based environmental projects, and promotion of climate-smart agricultural practices are among the approaches of the AIC. These climate-smart agricultural practices need to be aligned with and supported by national policy and a legal and regulatory framework. Policy and legislation can either slow down or accelerate the adoption of climate-smart agriculture. Promoting innovation requires effective partnerships with the government, the private sector, and universities. The case studies clearly show that there is a need for simultaneous action at the local and international levels on multiple challenges related to climate change. Climate change (CC) has negative impacts on agricultural production globally, nationally, and locally. Climate risks to agriculture, livestock, and fisheries are expected to increase over the coming decades.